2022
DOI: 10.1155/2022/1119038
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Salivary Biomarkers including Lactate Dehydrogenase and Hemoglobin A1c for Screening Chronic Periodontitis

Abstract: Aims: Periodontitis is one of the most common chronic bacterial infections in humans involving the tooth-supporting tissue. The present study aimed to evaluate and compare salivary biomarkers, including lactate dehydrogenase (LDH) and hemoglobin A1c (HbA1c), between patients with severe chronic periodontitis and healthy individuals. Methods: This study was performed on 29 patients with severe chronic periodontitis and 30 healthy individuals at Zahedan University of Medical Sciences, Zahedan, Iran, in 2021. Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The other biochemical marker that has been recently associated with the progression of clinical periodontitis is the enzyme LDH. A higher concentration of this enzyme is usually associated with cell necrosis and tissue degradation, which are closely related to the pathogenesis of this disease ( Ali et al, 2018 ; Moghadam et al, 2022 ). Our results showed that a significant increase in LDH levels was detected in the 42- and 56-day periodontitis-induced groups when compared to the corresponding controls, indicating a possible severe stage of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The other biochemical marker that has been recently associated with the progression of clinical periodontitis is the enzyme LDH. A higher concentration of this enzyme is usually associated with cell necrosis and tissue degradation, which are closely related to the pathogenesis of this disease ( Ali et al, 2018 ; Moghadam et al, 2022 ). Our results showed that a significant increase in LDH levels was detected in the 42- and 56-day periodontitis-induced groups when compared to the corresponding controls, indicating a possible severe stage of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Kugahara, Shosenj, Ohashi [ 28 ] found good results for screening of periodontitis in pregnant women using a diagnostic method based on salivary enzymes. Salivary biomarkers have been used to detect disease onset and progression, monitor response to therapy and measure susceptibility to the future progression of periodontitis [ 45 ]. Further studies are assessing their applicability in pregnant women and other populations [ 46 ].…”
Section: Discussionmentioning
confidence: 99%